American Economic Association Universal Academic Questionnaire Summary Statistics - Scott, Charles E; Siegfried, John J (American Economic Review, 2003)
American Economic Association Universal Academic Questionnaire Summary Statistics by Charles E. Scott and John J. Siegfried. Published in volume 93, issue 2, pages 521-524 of American Economic Review, May 2003